Pathophysiology of pulmonary embolism - Pratt, Gilberto (Cirugía del Uruguay, 1971)
The obstruc"tion of the arteropulmonary blood flow is the physiopathological element which is common to all pulmonary embolism. In many cases, apart from mechanical blockage, there is arteriolar vaso constriction which contributes to the increase , of vascular pulmonary resistence. Thus pulmonary hypertension due to vascular causes may appear, though its interpretation varies according to the intensity and severity of onset . Pathogenesis of pulmonary infarction and respiratory alteration following pulmonary embolism, are also analysed.